Incidentally detected bifid cardiac apex in a patient with acute myocardial infarction: A case presentation and brief literature review - Ali Hosseinsabet; Alireza Amirzadegan (KARE Publishing, 2018)
A bifid cardiac apex is a rare congenital cardiac anomaly in humans and is usually associated with other congenital heart diseases. Presently described is a case of an incidentally detected bifid cardiac apex in a patient presenting with inferior ST-segment elevation myocardial infarction, which was subsequently confirmed with selective ventriculography. This anomaly, because it is rare, can be a source of confusion to clinicians, especially when acute coronary syndrome is present. The possible presence of this anomaly should, therefore, be kept in mind in daily practice.